Comparative study of hematological parameters among smokers and nonsmokers in Basra city, Iraq - Safa Mohammed Hussein; Huda Hasan Aziz; Wurood Hameed Abed; Kadhim Fadhil Kadhim (Elsevier, 2024)
Background: Hematological parameters are significantly affected by both immediate and prolonged exposure to smoking. The objective of this investigation is to evaluate the influence of cigarette smoking on hematological parameters among male students enrolled at Basrah University in Iraq. Methods: The study comprised a total of seventy male participants, divided into two groups: smokers (n = 35) and nonsmokers (n = 35). Each participant provided a 5 ml venous blood sample to analyze the complete blood count using a hematology analyzer (Spinreact, Spincell 3). Results: Cigarette smokers exhibit notably elevated levels of Red Blood Cells (RBC) counts, Hemoglobin (HGB), Red Cell Distribution Width-CV (RDW-CV), granulocytes%, and platelets%, whereas Mean Corpuscular Volume (MCV) and lymphocytes% are notably lower among smokers. On the other hand, Hematocrit percentage (HCT), Mean Corpuscular Hemoglobin (MCH), Mean Corpuscular Hemoglobin Concentration (MCHC), and White Blood Cells (WBC) counts show no significant difference between cigarette smokers and nonsmokers. In contrast, Red Cell Distribution Width-SD (RDW-SD), Mid-range cell percentage (MID%), Mean Platelet Volume (MPV), Distribution Width (PDW), Platelet Plateletcrit percentage (PCT), Platelet-Lymphocyte Cell Ratio (P_LCR) and Platelet-Lymphocyte Cell Count (P_LCC) demonstrate no substantial variance between the two groups at the statistical significance threshold. Conclusion: This investigation concludes that tobacco cigarette smoking leads to detrimental alterations in hematological parameters, posing health risks.